2002
DOI: 10.1007/s00425-002-0766-9
|View full text |Cite
|
Sign up to set email alerts
|

Xylem embolism and drought-induced stomatal closure in maize

Abstract: Water relations during drought and xylem vulnerability to embolism were studied on four maize ( Zea mays L.) genotypes having contrasting grain yields under drought conditions. Drought provoked a drop in xylem pressure, leaf water potential and whole-plant transpiration. Transpiration was reduced to a minimum value when xylem pressures reached ca. -1.6 MPa. This value corresponded to the threshold xylem pressure below which xylem embolism developed to a substantial degree in leaf midribs. Therefore, xylem embo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 38 publications
8
77
0
2
Order By: Relevance
“…A large body of evidence indicates that xylem cavitation in the stem is common under water stress, and the role of desiccation-induced cavitation in leaves is supported by observation of embolism in major veins of plants (Canny 2001;Cochard 2002;Bucci et al 2003). Certainly, xylem cavitation is inevitable at some point as leaves desiccate, and studies of water potential relaxation data (including those shown here), indicate a dramatic loss of K leaf at water potentials less than −2 MPa.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A large body of evidence indicates that xylem cavitation in the stem is common under water stress, and the role of desiccation-induced cavitation in leaves is supported by observation of embolism in major veins of plants (Canny 2001;Cochard 2002;Bucci et al 2003). Certainly, xylem cavitation is inevitable at some point as leaves desiccate, and studies of water potential relaxation data (including those shown here), indicate a dramatic loss of K leaf at water potentials less than −2 MPa.…”
Section: Discussionmentioning
confidence: 53%
“…Extensive work on stems has shown that the conductivity of the xylem is critically dependent on water potential ( Ψ ), usually declining rapidly as Ψ inside the xylem apoplast falls below a threshold value (Sperry & Tyree 1988). Leaves are clearly sensitive to water stress-induced depression of hydraulic conductance (Linton & Nobel 2001;Cochard 2002;Brodribb & Holbrook 2003b;Lo Gullo et al . 2003;Brodribb & Holbrook 2004a), and due to the disproportionately large contribution leaves make to whole-plant hydraulic resistance, leaf vulnerability has the potential to dictate how plants respond to shortterm water stress.…”
Section: Introductionmentioning
confidence: 99%
“…Stomatal conductance has been shown to decline even in the absence of reduction in bulk leaf water potential (Davies, Mansfield & Hetherington 1990), suggesting that stomata are able to sense loss of root conductivity (Fuchs & Livingston 1996) through chemical signals transported from roots to leaves in the xylem sap (Zhang & Davies 1987). Although common negative relationships between stomatal behaviour and the degree of embolism have been found within species (Sperry, Alder & Eastlack 1993;Cochard 2002) and across different ages of the same species (Domec et al . 2004), no trends have yet been established across species.…”
Section: Introductionmentioning
confidence: 99%
“…An alternate view is that plants, especially crop plants, tend to maximize, rather than optimize, performance and "operate at the edge of dysfunction" [43]. In this view, an adaptive advantage conferred by stomata in angiosperms is to prevent catastrophic xylem embolism rather than respond to reduced hydraulic conductivities resulting from xylem cavitation [42] [44]- [46]. It should be borne in mind that while the present work is consistent with both the ideas of a feedback and feed-forward mechanism of stomatal control, the temporal resolution of the experiments did not allow disproof of either.…”
Section: Discussionmentioning
confidence: 99%